Implementasi Metode Fuzzy Sugeno dalam Aplikasi Mobile untuk Analisis Kinerja Sistem Antrian Puskesmas - Harahap, Adhelia Febriasari; Aryanti, Aryanti; Anugraha, Nurhajar (Forum Kerjasama Pendidikan Tinggi, 2024)
The registration process at health centers often faces efficiency issues, causing inconvenience for patients and reducing service productivity. Puskesmas is one such health facility that faces long queue problems almost every day, impacting the quality of service. This study aims to design and develop a health center queuing system based on the Internet of Things (IoT), allowing online registration through a mobile application based on Android and more efficient ticket acquisition. The Fuzzy Sugeno method is applied to evaluate and improve the performance of the queuing system. This application also provides notifications to patients about the time to enter the targeted clinic, thereby reducing waiting times and preventing loss of queue numbers. The implementation of the Fuzzy Sugeno method at Puskesmas has shown significant results in various service aspects. The average patient waiting time decreased from 90 minutes to 40 minutes, reflecting a reduction of 55.6%. Patient satisfaction increased from 3.2 to 4.5 on a scale of 5, or by 40.6%. Registration efficiency improved, with the time required decreasing from 10 minutes to 4 minutes per patient, resulting in a 60% increase in efficiency. Additionally, the service capacity increased, with the number of patients served per day rising from 70 to 100 patients, indicating an increase of 42.8%. The implementation of this technology has succeeded in creating more responsive, effective, and productive health services at Puskesmas, providing a positive impact on the community as a whole.